2005
DOI: 10.1093/poq/nfi002
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Telephone Survey Nonresponse over the Past Quarter Century

Abstract: The lengthy history and extended periods of relative design stability of the University of Michigan's Survey of Consumer Attitudes (SCA) make it an important resource for documenting response rate changes over the better part of survey research's history.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

48
452
2
8

Year Published

2007
2007
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 818 publications
(510 citation statements)
references
References 10 publications
48
452
2
8
Order By: Relevance
“…These findings suggest that trends observed regarding previous time periods (Curtin, Presser, and Singer 2005;de Heer 1999;Steeh et al 2001;Tortora 2004) have continued in recent years.…”
Section: Summary Of Findings and Implicationsmentioning
confidence: 60%
“…These findings suggest that trends observed regarding previous time periods (Curtin, Presser, and Singer 2005;de Heer 1999;Steeh et al 2001;Tortora 2004) have continued in recent years.…”
Section: Summary Of Findings and Implicationsmentioning
confidence: 60%
“…The overall cooperation rate 28 was 52.1 %, which is consistent with other telephone surveys. 29 The Alcohol Research Group has conducted two types of methodological studies which collectively suggest that biases in alcohol outcomes resulting from non-response and social desirability are likely to be minimal. The first, which used data from the 1995 and 2000 NAS, compared alcohol consumption between sample replicates (each a random subsample, "opened" during the study, and with a specific response rate) and found no significant association between replicate response rate and volume of alcohol consumption (unpublished).…”
Section: Samplementioning
confidence: 99%
“…The public is increasingly choosing not to respond to surveys (Curtin et al, 2005;de Leeuw and de Heer, 2002). In the face of this challenge, some survey organizations are trying to increase response rates by providing sample members with the mode they prefer.…”
Section: Introductionmentioning
confidence: 99%